Microbial food contamination - Wilson, Charles L.; Droby, Samir (CRC Press, 2008)
Evaluates the microbiology, biochemistry, detection, risk, and threat of foodborne illness in a global climate. This volume examines the pathogenic effect of contaminants, presents advances in detecting and monitoring of food borne human pathogens, and examines control and prevention measures